Basic Knowledge of Middle School English Teachers in Indonesia in Assessing Students ' Writing Ability - Harahap, Lena Marliana; Armin, Diah Safithri (VISION, 2023)
The capacity to plan lessons and assess students’ learning defines junior high school teachers’ professionalism. Because it significantly affects how they evaluate students’ writing learning outcomes, junior high school English teacher must have a solid foundation in assessing writing. 87 Junior high school teachers from the district and 38 junior high school teachers from the municipality were asked to participate in this quantitatively descriptive study by completing questionnaires regarding their fundamental writing assessment knowledge. Only 16.09% of district teachers and 26.32% of municipal teachers received scores above 60 as a result. These teachers still have significant difficulties planning, implementing, and evaluating writing even though they are all credentialed and routinely report significant professional activities. All stakeholders, particularly schools and the ministry of education.